Sedation at the end of life - Rada Ortega, Camilo; Perez toro, Lina Maria; Echeverri Saldarriaga, Sara; Reyes Marquez, Diana Carolina (CES Medicina, 2016)
Life expectancy has increased; consequently, the incidence of chronic illness has risen. Oncologic patients may present in their final days of life severe symptoms refractory to treatment, such as delirium, dyspnea, psychological stress and existential suffering. Sedation at the end of life is a strategy for the relief of those symptoms, highlighting that the intention is not to shorten life. We describe a pharmacological strategy for end-of-life sedation, along with ethics and legal aspects. DOI: http://dx.doi.org/10.21615/cesmedicina.30.1.5